Blood Pressure Reduction Does Not Reduce Perihematoma Oxygenation: A CT Perfusion Study. Issue 1 (January 2014) - Kate, Mahesh P; Hansen, Mikkel B; Mouridsen, Kim; Østergaard, Leif; Choi, Victor; Gould, Bronwen E; McCourt, Rebecca; Hill, Michael D; Demchuk, Andrew M; Coutts, Shelagh B; Dowlatshahi, Dariush; Emery, Derek J; et al.
Blood pressure (BP) reduction after intracerebral hemorrhage (ICH) is controversial, because of concerns that this may cause critical reductions in perihematoma perfusion and thereby precipitate tissue damage. We tested the hypothesis that BP reduction reduces perihematoma tissue oxygenation. Acute ICH patients were randomized to a systolic BP target of <150 or <180 mm Hg. Patients underwent CT perfusion (CTP) imaging 2 hours after randomization. Maps of cerebral blood flow (CBF), maximum oxygen extraction fraction (OEF max ), and the resulting maximum cerebral metabolic rate of oxygen (CMRO2 max ) permitted by local hemodynamics, were calculated from raw CTP data. Sixty-five patients (median (interquartile range) age 70 (20)) were imaged at a median (interquartile range) time from onset to CTP of 9.8 (13.6) hours. Mean OEF max was elevated in the perihematoma region (0.44±0.12) relative to contralateral tissue (0.36±0.11; P <0.001). Perihematoma CMRO2 max (3.40±1.67 mL/100 g per minute) was slightly lower relative to contralateral tissue (3.63±1.66 mL/100 g per minute; P =0.025). Despite a significant difference in systolic BP between the aggressive (140.5±18.7 mm Hg) and conservative (163.0±10.6 mm Hg; P <0.001) treatment groups, perihematoma CBF was unaffected (37.2±11.9 versus 35.8±9.6 mL/100 g per minute; P =0.307). Similarly, aggressive BP treatment did not affect perihematoma OEF max (0.43±0.12 versus 0.45±0.11; P =0.232) or CMRO2 max (3.16±1.66 versus 3.68±1.85 mL/100 g per minute; P =0.857). Blood pressure reduction does not affect perihematoma oxygen delivery. These data support the safety of early aggressive BP treatment in ICH.